MANAGEMENT TEACHING FACTORY IN IMPROVING THE COMPETENCY OF MECHANICAL ENGINEERING STUDENTS INDUSTRY AT NUSANTARA MANDIRI VOCATIONAL SCHOOL BONTANG - Andani, Darus Winanten Piandani; Komariyah, Laili; Bahzar, Moh. (International Journal of Cultural and Social Science, 2026)
The gap between student competency and industry encourages the implementationTeaching Factory (TeFa). This descriptive qualitative research aims to describe the management (planning, organizing, implementation, supervision) as well as the supporting and inhibiting factors of TeFa in the Industrial Mechanical Engineering Department of SMK Nusantara Mandiri Bontang. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The results of the study indicate: (1) collaborative planning according to practical needs; (2) organization through the formation of a special structure; (3) implementation involves curriculum alignment, 10 JP/month industrial learning, a block system, and two-stage PKL; (4) supervision is carried out in stages; (5) supporting factors include teacher competence and industry-standard facilities, while obstacles include limited funds and time for completing large projects.